2023
DOI: 10.1186/s13075-023-03079-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of pain neuroscience education followed by a Pilates exercises program in individuals with knee osteoarthritis: a pilot randomized controlled trial

Abstract: Background Knee osteoarthritis (OA) is a multifactorial form of rheumatic condition contributing to physical and psychological factors. Treatments have been provided solely and often compared with each other. An alternative view is that combined treatments addressing physical and psychological factors may result in more benefits. This study aimed to investigate the effect of pain neuroscience education (PNE) followed by Pilates exercises (PEs) in participants with knee OA, compared to PE alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…These outcomes are in line with previous studies that have reported unsatisfactory results on the efficacy of PNE in directly reducing pain and functional limitations. [25][26][27] Ponce-Fuentes et al conducted a randomized clinical trial in 29 patients with ARCR to compare effectiveness of the PNE versus biomedical education both in addition to the standard exercise program. 12 They found that either the PNE or biomedical education is equally effective in improving rest pain and disability, except for pain at movement in favor of the PNE group.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes are in line with previous studies that have reported unsatisfactory results on the efficacy of PNE in directly reducing pain and functional limitations. [25][26][27] Ponce-Fuentes et al conducted a randomized clinical trial in 29 patients with ARCR to compare effectiveness of the PNE versus biomedical education both in addition to the standard exercise program. 12 They found that either the PNE or biomedical education is equally effective in improving rest pain and disability, except for pain at movement in favor of the PNE group.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that both periodised circuit training and conventional strength training significantly decreased pain catastrophizing [ 168 ]. In relation to pain catastrophizing, it has been suggested that incorporating pain neuroscience education followed by Pilates exercises compared to Pilates exercises alone can result in statistically significant improvement in PCS [ 169 ]. The addition of action observation therapy to an exercise program for pain and related measures was also explored.…”
Section: Search Methodologymentioning
confidence: 99%